2010
DOI: 10.1007/s10393-010-0343-9
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Management for Malaria Control: Knowledge and Practices in Mvomero, Tanzania

Abstract: Environmental conditions play an important role in the transmission of malaria; therefore, regulating these conditions can help to reduce disease burden. Environmental management practices for disease control can be implemented at the community level to complement other malaria control methods. This study assesses current knowledge and practices related to mosquito ecology and environmental management for malaria control in a rural, agricultural region of Tanzania. Household surveys were conducted with 408 ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 18 publications
3
12
0
Order By: Relevance
“…These results are supported by various works done in Tanzania [4144]. Malaria is a particular problem in agricultural areas, as land use practices implemented often result in increased presence of breeding sites [6, 45]. The influence of agricultural systems on health is particularly notable via the intermediary process of land use change.…”
Section: Discussionsupporting
confidence: 59%
“…These results are supported by various works done in Tanzania [4144]. Malaria is a particular problem in agricultural areas, as land use practices implemented often result in increased presence of breeding sites [6, 45]. The influence of agricultural systems on health is particularly notable via the intermediary process of land use change.…”
Section: Discussionsupporting
confidence: 59%
“…In Africa, larval source management have been shown to be very effective in areas where mosquito breeding habitats are distinct and accessible [30]. Studies showed that when larval management is integrated with LLINs and IRS, a great improvement would be seen in malaria control efforts than IRS and LLINs alone [31,32]. The present study indicated that availability of distinct mosquito breeding habitats during the dry and wet seasons, indicating the potential use of larval source management to reduce the mosquito population.…”
Section: Discussionmentioning
confidence: 49%
“…For example, communities may organize a campaign for fighting bedbugs in villages most affected and/or plan for plastering the houses of families with poor housing conditions. The focus of “ Umuganda” in regards to destroying mosquito-breeding sites around homesteads has been promoted and should be maintained as the regulation of environmental conditions through management practices at community level could reduce disease burden [ 16 ].…”
Section: Discussionmentioning
confidence: 99%